PENDETEKSI KETINGGIAN LEVEL AIR DENGAN TAMPILAN LCD BERBASIS MIKROKONTROLLER ATMEGA 8 SERTA LED BUZZER DAN SEVEN SEGMENT SEBAGAI PERINGATAN DINI KENAIKAN AIR PASANG (ROB) BERBASIS PROGRAMMABLE LOGIC CONTROLLER CP1E-E40DR-A - Rahardjo, Rizal Fauzan Adi; Winarno, Heru (Vocational School Diponegoro University, 2012)
Rizal Fauzan Adi Rahardjo, Heru Winarno, in paper water level detection based atmega 8 microcontroller with lcd display, led, buzzer and seven segment as early warning of post water (rob) increase based CP1E-E40DR-A programmable logic controller explain that as a result of the overflow of the tidal sea water in rural areas sriwulan sayung District of Demak , the tidal water easily entered into the residential area , which can be fatal if not in further tackle. Tidal flood has become commonplace in the area Sriwulan Sayung District of Demak . However , the longer the tidal flood is troubling and very disturbing society . So I took the initiative to create a miniature tidal flood prevention . Height of the water level of a river that flows directly into the sea will be detected by the sensor. The sensors will send data to the PLC and will be displayed by the seven segment . Further increase in the water level of the river will also affect the water level in the ditch homes residents . Height of the ditch water level is detected by the sensor which will send data to the PLC and then displayed by seven segment LCD and previously through the microcontroller atmega 8. The maximum height of the water level gutter will be marked with berbunyinya buzzer and LED life. Keywords : Sensor , Seven Segment , Microcontroller Atmega 8 , LCD , LED, buzzer.